Collage Innovations Enhancing Preschool Fine Motor Skills Globally: Inovasi Kolase Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Secara Global - Adibah, Sarah; Iffatur Rocmah, Luluk (Indonesian Journal of Innovation Studies, 2024)
This study aims to explore the efficacy of collage activities using paper clay media in enhancing fine motor skills among 4-5-year-old children at TK Aisyiyah 2 Porong. Employing a classroom action research (CAR) design, the study progresses through planning, implementation, observation, and reflection stages. Data collection involved observation, documentation, and interviews, analyzed descriptively and quantitatively. The research found that fine motor skills significantly improved, with an average achievement in Cycle I at 70% and Cycle II at 83%. Teacher activity scores also increased from 2.3 to 3.8 between cycles. Results indicate the success of collage activities using paper clay in enhancing fine motor skills. The study underscores the importance of demonstration and practice methods in facilitating children’s understanding and proficiency in fine motor activities. The findings offer implications for educators and curriculum developers seeking to enhance fine motor skills in early childhood education through innovative, hands-on approaches. Highlight: Improved skills: Collage boosts fine motor skills in preschoolers effectively. Engaging methods: Demonstrations enhance understanding and engagement in motor activities. Innovative media: Paper clay fosters creativity and fine motor development effectively. Keywoard: Motor Skills, Collage, Paper Clay, Preschool, Action Research